Strategi Brand Awareness Melalui Pembuatan Logo dan Pemasaran Digital pada Mursi Collection di Desa Mojowangi Kabupaten Jombang - Tesalonika Devvany Nugroho; Nanda Putri Widianti; Karina Sanggraeini; Bintang Gymnastiar; Vincentia Stephani; Elvira Aprilia Primastika; Fitri Erliya Wati; Ilham Dio Bhakti; Zulfa Fayza Budiono; Dhian Satria Yudha Kartika (Lembaga Pengembangan Kinerja Dosen, 2024)
Digital Marketing is an effort for businesses to increase Brand Awareness, in the class digital marketing activities are also needed to increase demand and expand market reach.The purpose of this study is to provide an understanding of digital marketing to MSMEs in Mojowangi village and re-branding logos to increase brand awareness.The method used is observation and direct research in the field where this study describes the problems faced by Mursi Collection as an MSME actor with the Batik Ecoprint industry, namely the lack of brand visibility in front of the market so that it has an impact on operations by making logos, e-catalogues and Instagram accounts can increase brand awarenes.